Розробка автоматизованої системи управління зрошенням плодових культур - Сушко, Сергій Леонідович; Сушко, Сергей Леонидович; Sushko, Serhii (ТДАТУ, 2015)
UK: Робота присвячена розробці пристрою управління зрошенням, що визначає фізіологічні показники дерева і метеорологічні показники. За ціми показниками відбувається передача керуючого сигналу на виконавчі пристрої системи зрошення. RU: Работа посвящена разработке устройства управления орошением, определяющего физиологические показатели дерева и метеорологические показатели. По этим показателям определяются элементы управления орошением. EN: The article is devoted to arrangement working out for irrigating management defining trees physiological indices (water flowing speed in the trunk, temperature changes in the plant organ tissues) as well as meteorological indices. According to these indices the elements of irrigation management are being defined and the control signal transmission to irrigation system actuating mechanisms is being accomplished. The registration of incoming and outgoing information has been stipulated as well as functional and structural arrangement scheme has been worked out.
Разработка автоматизированной системы управления орошением плодовых культур
Automated system working out for fruit culture irrigating management
Keywords: зрошення; зрошення плодових культур; алгоритм зрошення; датчик; ксмлема; пристрій управління; кліматичні умови; автоматизація зрошення